Places that Matter: Place Attachment and Wellbeing of Older Antillean Migrants in the Netherlands - Lager, Debbie; van Hoven, Bettina; Meijering, Louise (European Spatial Research and Policy, 2012)
It has been argued that attachment to place increases wellbeing in old age (Wiles et al., 2009). Feeling ‘in place’ can increase an older person's wellbeing. For older migrants it can be a challenge to live in-between cultures. The objective of the article is to explore how older Antillean migrants derive a sense of wellbeing from attachment to their everyday places. We do so by drawing on in-depth interviews and a photography project with Antilleans who live in a senior cohousing community in a city in the Northern Netherlands. Based on the study, we conclude that the cohousing community acted as a central setting of experience from which the participants explored their wider surroundings and developed new attachments in the neighbourhood.